2016
DOI: 10.18632/oncotarget.9978
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-4516 involved autophagy associated with exposure to fine particulate matter

Abstract: Metals are vital toxic components of fine particulate matter (PM2.5). Cellular responses to exposure to PM2.5 or PM metal components remain unknown. Post-transcriptional profiling and subsequent cell- and individual-based assays implied that the metal ion-binding miR-4516/RPL37/autophagy pathway could play a critical role in cellular responses to PM2.5 and PM metal stresses. miR-4516 was up-regulated in A549 cells exposed to PM2.5 and in the serum of individuals living in a city with moderate air pollution. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“… 58 MiR-4516 expression was decreased in our incumbent firefighters, but was upregulated in a study of A549 cells exposed to PM 2.5 as well as the serum of persons living in a Chinese city with moderate air pollution. 59 MiR-145-5p expression was decreased in our incumbent firefighters, but increased in service members with polychlorinated dibenzodioxin (PCDD) and polychlorinated dibenzofuran (PCDF) exposures from open air burn pits comparing pre- and post-deployment. 60 However, to evaluate for dose–response relationships specific to firefighters, longitudinal studies including exposure assessment and measurement of miRNA changes are needed.…”
Section: Discussionmentioning
confidence: 92%
“… 58 MiR-4516 expression was decreased in our incumbent firefighters, but was upregulated in a study of A549 cells exposed to PM 2.5 as well as the serum of persons living in a Chinese city with moderate air pollution. 59 MiR-145-5p expression was decreased in our incumbent firefighters, but increased in service members with polychlorinated dibenzodioxin (PCDD) and polychlorinated dibenzofuran (PCDF) exposures from open air burn pits comparing pre- and post-deployment. 60 However, to evaluate for dose–response relationships specific to firefighters, longitudinal studies including exposure assessment and measurement of miRNA changes are needed.…”
Section: Discussionmentioning
confidence: 92%
“…Key miRNAs are miR-6090, which may play a role in embryo development 62; miR-4516, which is involved in autophagy63; miR-3960, which is related to Runx264, and miR-4459, which is involved in altering the stemness of embryonic stem cells65. However, the relationship between these microRNAs and chondrocytes remains unknown and needs to be further researched.…”
Section: Discussionmentioning
confidence: 99%
“…Using miRNA profiling analysis, we have identified that melatonin increases the expression of hsa‐miR‐4516, a major player in the regulation of PrP C expression, in MSC‐derived exosomes. Some studies have shown that miR‐4516 is involved in autophagy and is a potential biomarker for dust‐induced pulmonary fibrosis . A recent study has revealed miR‐4516 as a novel therapeutic target against glioblastoma .…”
Section: Discussionmentioning
confidence: 99%